UJI ADAPTASI BEBERAPA BAWANG MERAH (Allium cepa var Aggregatum L.) PADA MUSIM HUJAN (OFF SEASON) DI LAHAN KERING MASAM, LAMPUNG - Rismawita Sinaga; Nurmalita Waluyo; Ratna Wylis Arief; Gohan Octora Manurung (Politeknik Negeri Lampung., 2023)
The development of off season shallots is still low, this is constrained by the availability of adaptive seeds and appropriate cultivation techniques. The main objective of this study was to obtain adaptive, high-yielding shallot (Allium cepa var Aggregatum L.) in the off season in dry acid soil, Lampung. This research was conducted from February to May 2019 at the IP2TP Garden, Lampung Agricultural Technology Study Center, Natar, Bandar Lampung. This study was conducted using a completely randomized block design with five replications. The treatments consisted of five new purple varieties (VUB) of shallots registered by the Agricultural Research and Development Agency, including Violetta 1 Agrihorti (V1), Violetta 2 Agrihorti (V2), Violetta 3 Agrihorti (V3), Sembrani (V4) and Maja Cipanas ( V5). Observation parameters included growth components (plant height and number of tillers) and yield components (productivity) and shallot quality test (tuber diameter, number of tubers per 100g, percentage of rotten tuber, percentage of moldy tubers, shallot tuber color index, moisture content and tuber hardness index). The results showed that the red onion variety Violetta 3 Agrihorti was adaptive in the rainy season on dry acid soil because it had the best yield and physical quality compared to other varieties because it had the highest productiviy (12,89 ton/ha), the largest tuber diameter (2,2 cm), the lowest percentage of rotten tubers (6.24%) and the lowest percentage of moldy tubers (4.95%), redder tuber color, and lower hardness value or harder texture.